(0 and 1) or 0 =

0 or 0 = 0

so D

((0 and 1) --> (0 or (1 and 1)))=

( 0 --> (0 or 1)) =

( 0 --> 1) =1

so A

(P-->1) -->0

if P=0, then it is (0-->1) -->0 =

1 --> 0 = 0

if P=1, the it is (1-->1)-->0 =

1-->0 = 0

so either way the statement is false

so D

I've already done these for you...

why do you want to see them again

Olease R.

I needed you work them out like you did here ! explained it much better thank you so much. if you could explain the other ones out for me that would be great I posted those again also10/04/20